Effect of dietary energy and protein content on growth and carcass traits of Pekin ducks. (17th February 2015) - Zeng, Q. F.; Cherry, P.; Doster, A.; Murdoch, R.; Adeola, O.; Applegate, T. J.
Abstract : A study was conducted to determine the influence of dietary energy and protein concentrations on growth performance and carcass traits of Pekin ducks from 15 to 35 d of age. In experiment 1, 14-d-old ducks were randomly assigned to 3 dietary metabolizable energy (11.8, 12.8, and 13.8 MJ/kg) and 3 crude protein concentrations (15, 17, and 19%) in a 3 × 3 factorial arrangement (6 replicate pens; 66 ducks/pen). Carcass characteristics were evaluated on d 28, 32, and 35. In Experiment 2, 15-d-old ducks (6 replicate cages; 6 ducks/cage) were randomly allotted to the 9 diets that were remixed with 0.5% chromic oxide. Excreta were collected from d 17 to 19, and ileal digesta was collected on d 19 to determine AMEn and amino acid digestibility. In Experiment 1, there were interactions ( P < 0.05) between dietary metabolizable energy and crude protein (CP) on body weight (BW) gain and feed intake, wherein BW gain increased more to increasing dietary CP as dietary metabolizable energy increased. However, feed intake was only influenced by dietary crude protein at 11.8 MJ ME/kg and not 12.8 or 13.8 MJ/kg. As dietary CP increased from 15 to 19%, breast meat yield increased by 10.8% on d 35 ( P < 0.01). Conversely, increasing metabolizable energy from 11.8 to 13.8 MJ/kg increased dressing percentage, breast skin, and subcutaneous fat, but decreased breast meat yield (% but not weight) on d 35 ( P < 0.01). In Experiment 2, the determined AMEn for diets formulated to contain 11.8, 12.8, or 13.8 MJ ME/kg were 11.66, 12.68, and 13.75 MJ/kg, respectively; determined standardized ileal digestible Lys was 0.95, 1.00, and 1.21% for diets formulated to contain 15, 17, or 19% crude protein, respectively. The best body weight gain and feed conversion ratio was obtained when ducks were fed a high dietary AMEn (13.75 MJ/kg) and high CP (19%, 1.21% SID Lys). These results provide a framework for subsequent modeling of amino acid and energy inputs and the corresponding outputs of growth performance and carcass components.